Exploring Entrepreneurial Behavior in Rural Areas: Evidence from Private Higher Education Institutions in Henan Province, China - Liu, Chang; Jiang, Songyu; Phakdeephirot, Nutteera (Jurnal Ekuisci, 2025)
Background. Rural entrepreneurship has emerged as a strategic solution to alleviate employment pressure among university graduates in China. Aim. This study investigates the factors influencing rural entrepreneurial intention and behavior among private university graduates by extending the theory of planned behavior (TPB) to incorporate entrepreneurial passion and entrepreneurial value. Methods. A quantitative approach was employed, utilizing an online survey of 424 students from private higher education institutions in Henan Province. Structural equation modeling (SEM) was conducted to examine the relationships among subjective norms, perceived behavioral control, entrepreneurial attitude, entrepreneurial passion, entrepreneurial value, entrepreneurial intention, and entrepreneurial behavior. Result. The results confirm that entrepreneurial intention strongly predicts entrepreneurial behavior, with entrepreneurial passion and value exerting direct and indirect influences on both constructs. Conclusion. Additionally, subjective norms, perceived behavioral control, and entrepreneurial attitude significantly impact entrepreneurial intention. Implementation. These findings contribute to entrepreneurial research by expanding TPB to include psychological and value-driven factors while also offering practical insights for policymakers, educators, and rural development agencies.